Effect of Diabetes Mellitus on the Excretory Function of the Liver - Fidelis Oyakhire; Emokpae M.A; Enehizena Ogie; Egho E Valentine (Medical Laboratory Technology Journal, 2021)
Diabetes mellitus is an internationally recognized health problem and a leading cause of death worldwide. However, the most significant increase in prevalence is expected to occur in Asia and Africa, where most patients will be found by 2030. Diabetic Mellitus is a clinical and metabolic syndrome characterized by abnormal carbohydrate, protein, and fat metabolism resulting in hyperglycemia, increased protein breakdown, Ketosis or acidosis due to absolute or relative deficiency, and insulin resistance, thereby leading to vascular complications such as retinopathy, neuropathy, and nephropathy. This study evaluated the levels of plasma bilirubin, ALP, and GGT among diabetic patients. A total of eighty (80) individuals were recruited for the study comprising of forty (40) diabetes patients with age range 25-80 years and forty (40) control subjects with the age range of 20-30 years in Irrua/Ekpoma, Edo State, Nigeria. The study was carried out within six months (December 2018 - May 2019). All patients were diabetes. The serum Alkaline Phosphatase (ALP), gamma-glutamyl transferase (GGT), total and conjugated bilirubin were assayed by spectrophotometric method, and the data obtained were statistically analyzed using SPSS version 23.0 software. Serum levels of ALP, GGT, Total and unconjugated bilirubin were significantly elevated (P<0.05) among diabetes patients than control subjects except for conjugated bilirubin which was lower (P>0.05)  when compared with that of the control subjects. The mean serum levels of  ALP, GGT, total, unconjugated and conjugated bilirubin of male diabetes patients were non statistically significant (P>0.05) when compared with female diabetes subjects except the age (P<0.05). These findings indicate that hepatic injury was more likely among diabetes, and liver enzymes (ALP, GGT) are critical for monitoring glucose control concomitant with hepatic injury. Bilirubin is a potentially important biomarker for the assessment of the hepatic excretory system in diabetes mellitus.